Peran Guru Bimbingan dan Konseling dalam Meningkatkan Kesadaran Kesehatan Mental Siswa di Yogyakarta - Yuni Dwi Lestari; Eko Perianto (Indonesian Journal of Educational Counseling, 2026)
This study aims to describe the role of Guidance and Counseling teachers in increase students' mental health awareness in Yogyakarta. Mental health is a fundamental aspect in early adolescent development who experience various biological, cognitive, and socio-emotional changes. Guidance and Counseling teachers have a strategic position as facilitators of student development through preventive, curative, and collaborative services. This research used a qualitative approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Data analysis used data reduction, data presentation, and conclusions. Research informants consisted of one Guidance and Counseling teacher and eight seventh-grade students. The results showed that Guidance and Counseling teachers carry out their roles through: (1) preventive approaches with innovative classical services; (2) curative approaches through individual counseling and collaboration with psychology; and (3) collaborative approaches by establishing intensive communication with homeroom teachers, subject teachers, and parents